2021
DOI: 10.1177/2055668320985774
|View full text |Cite
|
Sign up to set email alerts
|

The SE-AssessWrist for robot-aided assessment of wrist stiffness and range of motion: Development and experimental validation

Abstract: Introduction Physical human-robot interaction offers a compelling platform for assessing recovery from neurological injury; however, robots currently used for assessment have typically been designed for the requirements of rehabilitation, not assessment. In this work, we present the design, control, and experimental validation of the SE-AssessWrist, which extends the capabilities of prior robotic devices to include complete wrist range of motion assessment in addition to stiffness evaluation. Methods The SE-As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…All the above studies have in common use of several tools to achieve the safety required by the medical procedure. The safety may be achieved through an effective correlation between the kinematics of the medical robot [18][19][20][21][22][23] and the control system [24][25][26][27][28][29][30][31] used to actuate the robotic structure with respect to human-robot interactions [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…All the above studies have in common use of several tools to achieve the safety required by the medical procedure. The safety may be achieved through an effective correlation between the kinematics of the medical robot [18][19][20][21][22][23] and the control system [24][25][26][27][28][29][30][31] used to actuate the robotic structure with respect to human-robot interactions [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…However, the concurrent validity between the robot-assisted technique and standard assessment methods needs to be further validated. A. Erwin et al [24] extends the capabilities of the existing robotic device SE-Assessment Wrist to achieve the complete wrist ROM assessment besides stiffness evaluation, while the future investigations still are needed to further investigate the reliability of these measurements. Therefore, robot-assisted measurements for the biomechanical properties, such as the ROM, stiffness, usually are based on the already developed robot system, and in this way, the time cost ,the accuracy and consistency of these measurement are considerable acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, several papers computed the viscoelastic properties at the wrist joint along different directions. They all concluded that the minor axis of the stiffness was directed along radial extension–ulnar flexion, a direction known as the motion of dart thrower’s wrist and oriented obliquely to the anatomical axes ( Crisco et al, 2011 ; Formica et al, 2012 ; Erwin et al, 2021 ). Thus, it would be interesting to test our protocol along the other directions of wrist movement and try to compare the results.…”
Section: Discussionmentioning
confidence: 99%